2013
DOI: 10.1111/clr.12148
|View full text |Cite
|
Sign up to set email alerts
|

Sequential healing of open extraction sockets. An experimental study in monkeys

Abstract: Modeling processes start from the lateral and apical walls of the alveolus, leading to the closure of the socket with newly formed bone within a month from extraction. Remodeling processes will follow the previous stages, resulting in trabecular and bone marrow formation and in a corticalization of the socket access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 18 publications
11
55
0
4
Order By: Relevance
“…This may be attributable to the depletion of bioactive factors secreted by the tissue with time, further suggesting the importance of cytokines in ESEHT efficacy. ESEHT at 2 weeks is constituted by CT matrix and a small amount of partially mineralized osteoid, 33–36 which will be replaced by mature bone rather than from CT healing. In the process of excavating the ESEHT, it was found that this healing tissue could be removed in blocks by digging with an excavator spoon, and its texture and shape could meet the requirements of occupying the space.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to the depletion of bioactive factors secreted by the tissue with time, further suggesting the importance of cytokines in ESEHT efficacy. ESEHT at 2 weeks is constituted by CT matrix and a small amount of partially mineralized osteoid, 33–36 which will be replaced by mature bone rather than from CT healing. In the process of excavating the ESEHT, it was found that this healing tissue could be removed in blocks by digging with an excavator spoon, and its texture and shape could meet the requirements of occupying the space.…”
Section: Discussionmentioning
confidence: 99%
“…Trials with animals to evaluate the phases of new bone formation in extraction sites have revealed that the woven bone, which is found in the bone defect area in the earliest phase, begins to be replaced with lamellar bone in 60-90 days. 46,47 In 120-180 days, the socket is filled with lamellar bone, and the new periosteum is already stable and in place. 46 Two recent reviews have confirmed that dimensional changes of soft and hard tissues may be faster in the first 3-6 months after extraction, followed by gradual reductions in dimensions thereafter.…”
Section: <005mentioning
confidence: 99%
“…Several human and animal studies have illustrated the healing process of the alveolar ridge after tooth extraction . This process has been described as a sequence of events including: coagulum formation, progressively substituted by a highly vascularized granulation tissue, subsequently replaced by provisional matrix and later by woven bone.…”
Section: Introductionmentioning
confidence: 99%